Caracterização e aplicação da lignina da palha de milho como coagulante e auxiliar de coagulação orgânico na remoção da turbidez de água - Diniz, Joice Pereira (Universidade Federal de São Carlos, 2026)
Water treatment plants (WTPs) are critical components of a municipality’s water supply system; they consist of the operational steps involved in treating surface water to ensure its quality and potability. One of these essential steps is coagulation, in which aluminum sulfate is commonly used. This coagulant presents both operational advantages and disadvantages for WTPs, raising the possibility of using plant-based polymers, such as lignin from corn stover. The objective of this study was to extract, modify, and apply lignin from corn stover as a coagulant and coagulation aid for turbidity removal. Extraction was performed using the soda pulping method, followed by chemical modification through oxidation with hydrogen peroxide. To validate the effects of the modification, the lignin was characterized using Ultraviolet-Visible Spectroscopy (UV-Vis), Nuclear Magnetic Resonance (¹H NMR), Thermogravimetric Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray Spectroscopy (EDS). Synthetic water was prepared, and batch Jar Tests were conducted using aluminum sulfate and lignin as primary coagulants to determine the optimal dosages for removal; subsequently, aluminum sulfate and lignin were applied as coagulation aids using the analysis of variance (ANOVA) methodology. The optimal dosages of aluminum sulfate were 80 mg. L⁻¹ for a settling time of 10 minutes and 50 mg. L⁻¹ for a settling time of 30 minutes; the lignins had no significant effect on turbidity removal, and their role as a coagulation aid was also ineffective, as confirmed by ANOVA with hypothesis testing (p-value > 0.05). Therefore, it was concluded that lignin was not capable of removing turbidity from the synthetic water within the predetermined times in the Jar Test. It is recommended that future studies use a turbidity level close to 100 NTU and evaluate the effects of lignin by altering the operational conditions of the Jar Test, such as pH.
Characterization and application of corn straw lignin as an organic coagulant and coagulation aid for water turbidity removal
Keywords: Zea mays L; Coagulante orgânico; Jar Test; Organic coagulant; CIENCIAS EXATAS E DA TERRA::QUIMICA; 11. Cidades e Comunidades Sustentáveis